Generalised tissue abnormality of aryl hydrocarbon hydroxylase in psoriasis. Issue 6251 (15th November 1980) - Chapman, P H; Kersey, P J; Keys, B; Shuster, S; Rawlins, M D
Abstract : Microsomal aryl hydrocarbon hydroxylase (AHH) activity and inducibility were measured in jejunal mucosa, liver, and lesion-free epidermis of patients with psoriasis. In all three tissues AHH activity and inducibility were less than in controls. This demonstration of a generalised enzymatic abnormality in the tissues of patients with psoriasis is in keeping with the suggestion that it may be close to the underlying genetic defect.